Professional quality of life and organizational changes: a five-year observational study in Primary Care - Cortes-Rubio Jose; Beamud-Lagos Milagros; Gomez-Gascon Tomas; Martin-Fernandez Jesus; Alberquilla-Me (BMC, 2007)
Abstract Background The satisfaction and the quality of life perceived by professionals have implications for the performance of health organizations. We have assessed the variations in professional quality of life (PQL) and their explanatory factors during a services management decentralization process. Methods It was designed as a longitudinal analytical observational study in a Health Area in Madrid, Spain. Three surveys were sent out during an ongoing management decentralization process between 2001 and 2005. The professionals surveyed were divided into three groups: Group I (97.3% physicians), group II (92.5% nurses) and group III (auxiliary personnel). Analysis of the tendency and elaboration of an explanatory multivariate model was made. The PQL -35 questionnaire, based on Karasek's demand-control theory, was used to measure PQL. This questionnaire recognizes three PQL dimensions: management support (MS), workload (WL) and intrinsic motivation (IM). Results 1444 responses were analyzed. PQL increased 0.16 (CI 95% 0.04 - 0.28) points in each survey. Group II presents over time a higher PQL score than group I of 0.38 (IC 95% 0.18 - 0.59) points. There is no difference between groups I and III. For each point that MS increases, PQL increases between 0.44 and 0.59 points. PQL decreases an average of between 0.35 and 0.49 point, for each point that WL increases. Age appears to have a marginal association with PQL (CI 95% 0.00 - 0.02), as it occurs with being single or not having a stable relationship (CI 95% 0.01 - 0.41). Performing management tasks currently or in the past is related to poorer PQL perception (CI 95% -0.45 - -0.06), and the same occurs with working other than morning shifts (CI 95% -0.03 - -0.40 points). PQL is not related to sex, location of the centre (rural/urban), time spent working in the organization or contractual situation. Conclusion With the improvement in work control and avoiding increases in workloads, PQL perception can be maintained despite deep organizational changes at the macro-management level. Different professional groups experience different perceptions depending on how the changes impact their position in the organization.